E-097 Identifying blood pressure thresholds for better thrombectomy outcomes. (23rd July 2022) - Killedar, A; Fuchs, V; Shah, S; Hill, M; Pema, P; Budzik, R; Alhajeri, A; Koss, A; Dedhia, N; Loochtan, A; Rai, V; Katz, B; et al.
Abstract : Background: We sought to determine if a pre-reperfusion blood pressure threshold exists for large vessel occlusion, acute ischemic stroke (LVO AIS) patients which independently prognosticates a good clinical outcome. Methods: We retrospectively reviewed patients from July 2013 to December 2015 that were treated with a thrombectomy for a middle cerebral artery M1 (MCA M1) occlusion at our comprehensive stroke center (CSC). We obtained pre-procedure arterial blood pressure from available records at the time of EMS activation to the time of reperfusion and calculated an average ischemic time mean arterial pressure (MAP). All patients in our series underwent a cerebral angiogram to assess collateral status prior to initiating thrombectomy. We also defined angiographic arterial collateral status to the middle cerebral artery distribution as robust if any leptomeningeal supply from the anterior or posterior circulation extended into the pre-sylvian divisions and marginal if leptomeningeal supply did not reach the sylvian fissure. All patients included in our analysis, achieved TICI 2b or better reperfusion. Our endpoint was a modified Rankin Scale (mRS) < 2 at 90 days. For analysis, the averaged mean arterial pressure (MAP) range was segmented and dichotomized into the following groups: greater than 85mmHg, 90mmHg, 95mmHg, 100mmHg, 110 mmHg and 115mmHg. We considered 60-minute time epochs from symptom onset to thrombectomy completion, pre-treatment ASPECTS score, t-PA treatment and collateral status. Significant parameters from a univariate analysis of the above were included into a multivariate logistic regression to determine which variables significantly influenced a better outcome. Results: We reviewed 52 patients. The mean age was 70±14; NIHSS was 16±6; 40% (21) received t-PA; 58% (30) had robust collaterals; the median ASPECTS score was 10±1; TICI 3 score was achieved in 63% (33) and 67% (35) had a mRS of < 2 at 90 days. The number of patients having a mean arterial blood pressure threshold were as follows: >85mmHg [96% (50)], >90mmHg [83% (43)], >95mmHg [73% (38)], >100mmHg [58% (30)], >110mmHg [31% (16)] and >115mmHg [15% (8)]. The number of patients that were within a particular temporal threshold from symptom onset to end of mechanical thrombectomy were as follows: 3hrs [4% (2)], 4hrs [21% (11)], 5hrs [39% (20)], 6hrs [52% (27)], 7hrs [67% (35)], 8hrs [79% (41)], 9hrs [87% (45)] and 12hrs [90% (47)]. We used binomial logistic regression for the above variables. After considering positive univariates from above, our multivariate logistic regression model identified that mean arterial pressure threshold more than 95mmHg was the sole factor that was statistically significant to determine a better outcome post thrombectomy procedure [OR 15.1, CI 1.3- 170.1, p=0.02 ]. The rate of good clinical outcome in those patients with a mean arterial blood pressure maintained above 95mmHg was 76% and 43% in those below the threshold [χ 2 (MAP >95mmHg associated with mRS< 2) =5.2, p=0.02 ]. Conclusion: Our analysis suggests that there may be a mean arterial blood pressure threshold that, if maintained, can improve clinical outcomes in thrombectomy patients. Further prospective studies may identify an appropriate target for therapy prior to procedure. Disclosures: A. Killedar: None. V. Fuchs: None. S. Shah: None. M. Hill: None. P. Pema: None. R. Budzik: None. A. Alhajeri: None. A. Koss: None. N. Dedhia: None. A. Loochtan: None. V. Rai: None. B. Katz: None. W. Hicks: None. B. Raetzke: None. N. Vora: None.